2020
DOI: 10.3389/fimmu.2020.00835
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Atlas Reveals Complexity of the Immunosuppressive Microenvironment of Initial and Recurrent Glioblastoma

Abstract: The Glioblastoma (GBM) immune microenvironment plays a critical role in tumor development, progression, and prognosis. A comprehensive understanding of the intricate milieu and its interactions remains unclear, and single-cell analysis is crucially needed. Leveraging mass cytometry (CyTOF), we analyzed immunocytes from 13 initial and three recurrent GBM samples and their matched peripheral blood mononuclear cells (pPBMCs). Using a panel of 30 markers, we provide a high-dimensional view of the complex GBM immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 43 publications
7
97
0
1
Order By: Relevance
“…Alternatively, stimuli such as IL-4, IL-14, IL-10 can induce macrophages towards an anti-inflammatory and cancer-promoting M2 phenotype (41,42). In GBM, TAMs were the predominant infiltrating immune cells and usually polarized to an immunosuppressive M2-like phenotype (43,44). This study shows that PD-L1 may be an important regulator of macrophages in GBM, supported by the positive correlation between them.…”
Section: Discussionsupporting
confidence: 62%
“…Alternatively, stimuli such as IL-4, IL-14, IL-10 can induce macrophages towards an anti-inflammatory and cancer-promoting M2 phenotype (41,42). In GBM, TAMs were the predominant infiltrating immune cells and usually polarized to an immunosuppressive M2-like phenotype (43,44). This study shows that PD-L1 may be an important regulator of macrophages in GBM, supported by the positive correlation between them.…”
Section: Discussionsupporting
confidence: 62%
“…Although necessary approximations are made, the estimation is accurate as indicated by its consistency with the result of computer simulation and of patient data from real experiments. Results from previous single-cell studies are also consistent in the ballpark with Sensei's predictions[38]. Sensei runs in seconds on the front-end without requiring any connection to backend servers, providing versatile, secured utilities for researchers with limited resources.…”
supporting
confidence: 73%
“…The strong effector functions are lost and various inhibitory receptors are expressed in exhausted T cells (T EX ) ( 33 ). Fu et al suggested that the tumor tissue showed high percentages of T EX and Treg cells compared to those in the peripheral blood ( 34 ), suggesting that tumor tissue showed relatively more immunosuppressive phenotypes. Consistently, CD8 + T EX cells were identified from the tumor tissue but not from the peripheral blood, in our study.…”
Section: Discussionmentioning
confidence: 99%